Institutional Responses to Aging Populations and Economic Growth: A Panel Data Approach - Patrick M. Emerson; Shawn D. Knabb; Anca-Ioana Sirbu (Institute of Labor Economics (IZA), 2019)
Will an aging population lower economic growth? Economists are generally concerned that the increase in life expectancy could lower economic growth, however, theory does not make a prediction. As life expectancy increases, so should household savings, which results in more physical capital per worker. This will stimulate economic growth. However, as the retired population share increases, this may reduce spending on children as more resources are transferred to the elderly. This will likely reduce human capital accumulation and lower growth. The net effect of these competing influences is an empirical question. This paper constructs a stylized endogenous growth model that includes both human capital and government transfers to the elderly. The model is mapped into a linear statistical framework that allows us to estimate each of these potential responses using panel data for a set of OECD countries during the period 1975-2014. We find evidence that households do in fact increase savings in response to a longer retirement period and this effect is associated with a higher realized rate of growth per worker. However, we also find evidence that an aging population reduces spending on children (or other productive investments) placing a drag on growth. These results suggest it is the institutional response to population aging that will determine whether or not an aging population will place a drag on future growth, not population aging itself.
Keywords: J11; J18; I21; I28; E66; E37; O43; 330; population aging; educational crowding-out; slow secular growth; cross-country panel data